Prayer Chanting of Two Jewish-Sephardi Traditions- Music, History and Culture - Essica Marks (Current Research in Language, Literature and Education Vol. 6, 2022)
The study of a Jewish liturgical genre that is performed in the main sections of Jewish prayer services is presented in this article. "Prayer chanting" is the liturgical term for this liturgical genre. In Jewish prayer services, the phrase refers to the cantor’s musical rendering of the prose readings. Most Jewish liturgical traditions have a prayer chanting genre, and its essential characteristic is a close attachment of the musical structure to the text’s structure. The purpose of this article is to look at the musical, cultural, and historical qualities of two Sephardi Jewish traditions’ prayer chanting, and to explain how this liturgical genre reflects historical and cultural features of these liturgical traditions. The research given here is based on field work that included prayer recordings, interviews with well-known cantors from both liturgical traditions, and observations in synagogues from both liturgical traditions. It is important to the field of Jewish music that this genre of the liturgical music of the Moroccan Jews will be the target of future study.